1982
DOI: 10.1002/ajh.2830120208
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the cells in chronic neutrophilic leukemia

Abstract: Light and electron microscopy of neutrophils from chronic neutrophilic leukemia (CNL) did not reveal differences from normal mature neutrophils. However, functional characterization of CNL cells showed marked differences when compared to normal cells. CNL neutrophils were much less viable in suboptimal conditions. Their survival was further reduced by autologous serum and was corrected by normal human serm. CNL cells showed very active phagocytosis, but their bactericidal activity was reduced in suboptimal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
1
20
1
Order By: Relevance
“…Published studies of neutrophil function in CNL have been limited to one or two cases each. Dotten et al [3] reported normal phagocytosis, slightly decreased bacterial killing and increased granule release in response to immune complexes. Kaplan and Chervenick [7] also ob served slightly decreased bacterial killing but found the metabolic burst to be normal to a phagocytic stimulus, confirming earlier results [4].…”
Section: Introductionmentioning
confidence: 99%
“…Published studies of neutrophil function in CNL have been limited to one or two cases each. Dotten et al [3] reported normal phagocytosis, slightly decreased bacterial killing and increased granule release in response to immune complexes. Kaplan and Chervenick [7] also ob served slightly decreased bacterial killing but found the metabolic burst to be normal to a phagocytic stimulus, confirming earlier results [4].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with other MPD often have haemor rhagic complications and since the majority of these patients are middle-aged or older, they may require medication for back pain and joint problems, which could interfere with the platelet function and aggra vate the bleeding tendency. 5 of the 17 CNL patients reported previously have died due to a bacterial infection [1,3,14], Although our patient has never had an infective process, the neutrophils showed active phagocytosis, but intracel lular killing was reduced. Abnormalities of neutrophil granules described which predispose patients to in fections include lactoferrin deficiency due to absence of specific granules [15] and peroxidase deficiency with absence of or abnormal depletion of azurophil granules [16], It could be speculated that this may be the cause of serious infections in CNL.…”
Section: Discussionmentioning
confidence: 98%
“…In 1 case the attempt was made so close to the onset of blast transformation that failure might be due to the development of the acute phase [4], In another case three attempts to culture bone marrow during a 16-month period, prior to the development of blast crises, was unsuccessful [5] but in a further case CNL cells grew easily [3]. In our patient peripheral blood tested twice at a 6-month interval and bone marrow tested once all showed reduced numbers of CFU-C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) In this case, phagocytosis, chemotaxis and respiratory burst activity (superoxide production) were increased, especially in the absence of stimulation (spontaneous respiratory burst activity), whereas microbial killing activity was similar to that of normal control neutrophils. Normal or elevated phagocytosis and respiratory burst activity [5][6][7][8] and decreased bactericidal activity of neutrophils 4,6,7) have been reported in patients with CNL. Differences in neutrophil function may be due to differences in the pathophysiology of each patient or to technical differences in the assessment of neutrophil function.…”
Section: Discussionmentioning
confidence: 99%